New resources in combined therapy of osteoarthrosis - Suschuk, Yevgeny (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The effect of the combination therapy of glucosamine sulfate in combination with diclofenac or escin on the intensity of pain in osteoarthritis. A total of 4931 patients entered a mean age of (57 ± 12,97) years. Used treatment which comprises administering intramuscular glucosamine sulfate (400 mg 3 times a week) for four weeks per os (1500 mg 1 time per day) for 8 weeks, and the application of diclofenac (spray 1% 3-4 times daily for 2 weeks) or escin gel locally 2-3 times a day for 8 weeks in the affected joints. Pain intensity was assessed using a numerical rating scale. Found that in the case of both treatments is significantly reduced levels of pain in patients with osteoarthritis of the end of the study (p <0,001). Safety of the combination therapy was high.